Contribution of Fetal Tricuspid Regurgitation in First Trimester Screening for Major Cardiac Defects in Ulaanbaatar - Shirchinjav, Altantuya; Tovuudorj, Bolormaa; Tudevdorj, Erkhembaatar (Central Asian Journal of Medical Sciences, 2017)
Objective: To estimate the potential value of fetal assessment for tricuspid regurgitation, nuchal translucency and ductus venosus at 11-13 weeks of gestation in the prediction of major cardiac defects. Methods: Prospective cohort study data was derived from first-trimester screening of pregnant women at National Center for Maternal and Child Health between March 2014 to May 2017. A total of 318 patients at 110 to 136 weeks of gestation enrolled in the study. Trans abdominal ultrasonography (using 3 to 7.5 MHz curvilinear transducers) was performed to indirectly measure gestational age using the fetal crown-rump length, measure the fetal nuchal translucency thickness, and to assess blood flow across the tricuspid valve in 304 live fetuses in singleton pregnancies. Results: The median age of the mothers was 34 (range, 19-46 years). Crown-rump length of ranged from 45-84 mm. Eight (3.2%) of the 304 fetuses were diagnosed with major heart defects and increased nuchal translucency and tricuspid regurgitation were shown to be strongly associated with CHD. Increased nuchal translucency was present in 83% of fetuses with CHD (p=0.0001), while tricuspid regurgitation was present in 73% of those same fetuses (p=0.012). Conclusion: First trimester fetal ultrasound biomarkers can be sued to screen for major heart defects. Increased NT and TR are important indicators of the need for echocardiography, which is useful for early prenatal diagnosis of CHD.